MICA TIGANIADA OU L’AVENTURE DU FOLK-ROCK ROUMAIN PENDANT LA PÉRIODE COMMUNISTE - Luana STAN (Studia Universitatis Babeş-Bolyai. Musica)
Mica Tiganiada is a Romanian folk-rock music composed by Phoenix in 1972, during the communist era, when rock music was forbidden. Therefore, the composers had to adapt their rock music to the “accepted” items: the folklore. This is an excellent example of mixing the aksak rhythm, the rock ensemble, the women choir and the violin into a coherent piece of music.